2014
DOI: 10.1097/jto.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes for Patients With Thymic Carcinoma: Evaluation of Masaoka Staging

Abstract: Background Thymic carcinomas are rare cancers with limited data regarding outcomes, particularly for those patients with advanced disease. Methods We identified patients with thymic carcinomas diagnosed between 1993 and 2012. Patient characteristics, recurrence free survival (RFS), and overall survival (OS) were analyzed. Results One hundred twenty-one patients with thymic carcinomas were identified. Higher Masaoka stage was associated with worse OS and RFS (5-yr OS of 100%, 81%, 51%, 24%, and 17% for stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…The poor prognosis of thymic carcinoma emphasizes the dilemma of the lack of effective systemic treatment options. 10,11 Paclitaxel is a cytoskeletal drug that targets tubulin. Its mechanism of action involves interference with the normal breakdown of microtubules during cell division.…”
Section: Discussionmentioning
confidence: 99%
“…The poor prognosis of thymic carcinoma emphasizes the dilemma of the lack of effective systemic treatment options. 10,11 Paclitaxel is a cytoskeletal drug that targets tubulin. Its mechanism of action involves interference with the normal breakdown of microtubules during cell division.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Kit was also used as a diagnostic tool of these tumors [39,93] [8,31,67]. Nine studies reported that the staging wasn't a relevant prognostic factor [6,9,19,20,30,46,57,71,74]. These studies reported that the vascular invasion was a bad prognosis factor and that it needs to be integrated in the staging system [46,57,71].…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the rarity of thymic carcinomas that account for 1 to 4% of all malignant tumors of the thymus and between 10 to 20% of thymic epithelial tumors [11,12,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. .…”
Section: Discussionmentioning
confidence: 99%
“…Thymic carcinoma prognostic factors include Masaoka-Koga stage [11, 12], resection status [11, 13], pathological subtype [1], and innominate vessel invasion [8]. Most patients with thymic carcinoma present with advanced disease at initial diagnosis.…”
Section: Introductionmentioning
confidence: 99%